Use of Laboratory Models in the Design of Potable Water Treatment Plants - Mečíř, Filip (Vysoké učení technické v Brně,Fakulta stavební, 2024)
The aim of this article was to investigate the potential of laboratory water treatment testing methods to support the design of a drinking water treatment plant. The work investigated jar tests, dissolved air flotation, membrane processes and adsorption on activated carbon. The use of laboratory tests allows the optimization of the design of the drinking water treatment plant and reduces the costs of further stages of project preparation. These tests result in projected chemical consumption, energy consumption and waste production estimates. All these values are important for the design of the treatment plant.
Keywords: Jar test; DAF; potable water treatment; design phase